2019
DOI: 10.3892/ijo.2019.4860
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human zinc finger nfx‑1‑type containing 1 encoding ZNFX1 gene and its response to 12‑O‑tetradecanoyl‑13‑acetate in HL‑60 cells

Abstract: Human promyelocytic HL-60 cells can be differentiated into macrophage-like cells by treatment with 12-O-tetra decanoylphorbol-13-acetate (TPA). Certain 5' upstream regions of the zinc finger protein (ZNF)-encoding genes contain duplicated GGAA motifs, which are frequently found in the TPA-responding gene promoter regions. To examine transcriptional responses to TPA, 5'flanking regions of human zinc finger CCCH-type containing, antiviral, ZNF252, ZNF343, ZNF555, ZNF782 and zinc finger nfx-1-type containing 1 (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…7 ZNFX1 expression is low in uninfected cells but is rapidly upregulated in response to viral infections and exposure to type I interferons. 8 ZNFX1 binds to viral RNA and interacts with the mitochondrial antiviral signaling (MAVS) protein, promoting the expression of interferon-stimulated genes (ISGs). Signaling downstream of ZNFX1 does not depend on 2 other MAVS-associated cytosolic viral sensors (retinoic acidinducible gene I [RIG-I] and melanoma differentiationassociated protein 5 [MDA5]).…”
mentioning
confidence: 99%
“…7 ZNFX1 expression is low in uninfected cells but is rapidly upregulated in response to viral infections and exposure to type I interferons. 8 ZNFX1 binds to viral RNA and interacts with the mitochondrial antiviral signaling (MAVS) protein, promoting the expression of interferon-stimulated genes (ISGs). Signaling downstream of ZNFX1 does not depend on 2 other MAVS-associated cytosolic viral sensors (retinoic acidinducible gene I [RIG-I] and melanoma differentiationassociated protein 5 [MDA5]).…”
mentioning
confidence: 99%
“…In addition, RELB is required for TNF-induced differentiation of bone marrow cells into M1 macrophages in mice ( 33 ). Our previous studies indicated that the duplicated GGAA-motif is responsible for the activation of the E2F4 and ZNFX1 genes during TPA-induced macrophage-like differentiation of HL-60 cells ( 34 , 35 ). In HeLa S3 cells, the Sp1/PU.1 ratio is notably increased following the Rsv treatment ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts with highest module membership in the greenyellow module all represent orthologs to elements of the Interferon (IFN) Mediated response to RNA viruses. Several innate immune mobilized antiviral zinc finger protein orthologs are represented in this module, including PARP12 , ZC3HAVIL , TUT4 , and three orthologs of ZNFX1 , one of which is the hub transcript [ 249 , 252 , 292 , 293 ]. Other transcripts are orthologs of interferon-stimulated genes (ISG) that stimulate or facilitate the expression of other ISG, including ZNFX1 , MRE11 , DTX3L , CMTR1 , and IRF1 [ 222 , 226 , 229 , 244 , 248 ].…”
Section: Discussionmentioning
confidence: 99%